2006
DOI: 10.1007/s00198-006-0247-2
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral bone mineral density and its predictors in healthy school girls from two different socioeconomic groups in Delhi

Abstract: In conclusion, age, nutrition, height and weight are significantly associated with BMD at peripheral sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 38 publications
1
12
1
Order By: Relevance
“…1 Correlation of BMD at forearm by peripheral DXA and total body BMD by central DXA 0.101 g/cm 2 to 0.967±0.107 g/cm 2 , depending on the model and manufacturer of the DXA machine used, which is significantly lower than that reported in US and European populations [11,[29][30][31]. This could be attributed to differences in frame size, height, vertebral size, hip width and BMI [8,32], and nutritional and genetic factors [9,10,17]. Hence, applying peak BMD data of Caucasians to define cutoffs for osteoporosis and osteopenia in Indian population remains an issue for debate [7,29].…”
Section: Calcaneum Bmdmentioning
confidence: 81%
See 1 more Smart Citation
“…1 Correlation of BMD at forearm by peripheral DXA and total body BMD by central DXA 0.101 g/cm 2 to 0.967±0.107 g/cm 2 , depending on the model and manufacturer of the DXA machine used, which is significantly lower than that reported in US and European populations [11,[29][30][31]. This could be attributed to differences in frame size, height, vertebral size, hip width and BMI [8,32], and nutritional and genetic factors [9,10,17]. Hence, applying peak BMD data of Caucasians to define cutoffs for osteoporosis and osteopenia in Indian population remains an issue for debate [7,29].…”
Section: Calcaneum Bmdmentioning
confidence: 81%
“…It is projected that more than about 50% of all osteoporotic hip fractures in the world will occur in Asia by the year 2050 [2]. Most studies in healthy Asian and Indian adults, who have high prevalence of hypovitaminosis D [6, 7; Marwaha et al, submitted for publication] have revealed lower BMD than white Caucasian subjects [8][9][10][11][12]. In view of paucity of data on BMD in elderly population [12][13][14][15][16][17] and reports of osteoporotic fractures occurring a decade earlier in Indian men and women compared to white Caucasians [18], we undertook this study in men and postmenopausal women more than 50 years of age to assess prevalence of osteoporosis/osteopenia in elderly population and to find correlation of BMD with anthropometric and biochemical parameters.…”
Section: Introductionmentioning
confidence: 98%
“…Also, SES had a significant independent effect on whole body bone size in poor urban South African children [31]. Similarly, a study from India reported that adolescent girls with higher SES had significantly higher distal forearm BMD [32].…”
Section: Discussionmentioning
confidence: 93%
“…Some studies reported positive associations among SES and bone-related variables (i.e., bone age, whole-body BMC and BMD, and distal forearm and calcaneus BMD) in children and adolescents, after taking into account the role of confounders, such as age, sexual maturation, height, and weight [12][13][14][15]. In addition, Arabi et al [36] showed that boys and girls of higher SES tended to have higher BMD than those from a lower SES at the subtotal body (whole body minus head), lumbar spine, forearm, total hip, femoral neck, and trochanter sites.…”
Section: Discussionmentioning
confidence: 98%
“…Because of its influence on PA and nutrition, it can be hypothesized that SES may play a role in the development of bone mass, yet this association is still poorly understood. Some studies have observed that the higher the SES, the higher the bone mass in children and adolescents [12][13][14][15], whereas others have observed the opposite [16] or no association [13,17,18]. Some of these studies have not taken into account relevant confounders, such as PA or lean mass, which make comparison and interpretation of the results difficult.…”
mentioning
confidence: 89%